Is it time to revisit the Boston Carpal Tunnel Questionnaire? New insights from a Rasch model analysis. Issue 4 (2nd February 2021) - Jerosch‐Herold, Christina; Bland, Jeremy D. P.; Horton, Mike
Abstract: Background: The Boston Carpal Tunnel Questionnaire (BCTQ) is a patient‐reported outcome measure (PROM) used to measure symptom severity and function in carpal tunnel syndrome (CTS). Despite its wide use, investigation of its measurement properties using modern psychometric methodologies is limited. Methods: Completed BCTQ data collected routinely in the Canterbury carpal tunnel clinic was used to investigate the structural validity and measurement properties of the BCTQ through application of a Rasch model analytic approach. Results: A total of 600 patients with electrodiagnostically confirmed CTS in their right hand were randomly selected from the database and analyzed. Mean age was 48.8 y, and 73% were women. Initial analysis showed that the 19 items could not be reliably added up to form a single linear construct. All subsequent analyses were done by subscale only. The Symptom Severity Subscale (SSS) displayed a large amount of local dependence. This could be accommodated through the creation of four clinically derived testlets, allowing for the ordinal SSS raw score to be transformed to a linear measure. The Functional Status Subscale (FSS) displayed a number of issues regarding its psychometric integrity. These include scale and item fit, targeting, differential item functioning, and dimensionality. Conclusions: This study shows that a single total score generated across all BCTQ items is not psychometrically valid, and that the SSS and FSS subscales should be treated separately. We propose a modified scoring system for the SSS, resulting in a linear measure that can be used in the analysis of future and existing datasets.